Are 2020's medical students still suffering from gender stereotypes? An Italian study. (20th October 2021) - Boietti, E; Bert, F; Gualano, M R; Pompili, E; Rousset, S; Franzini Tibaldeo, E; Tatti, R; Siliquini, R
Abstract: Background: Gender medicine is crucial to reduce health inequalities in Europe. Knowledge about medical students' attitudes and beliefs regarding sex and gender is important to improve gender medicine courses. The aim of this study is to evaluate gender awareness and its predictors in Italian medical students. Methods: During 2020, we performed a cross-sectional study among medical students from the University of Turin, Italy. We used the validated Nijmegen Gender Awareness Scale in Medicine (N-GAMS) to investigate gender sensitivity (GS) and gender role ideology towards patients (GRIP) or doctors (GRID). Multivariable logistic regression model was performed to explore potential predictors of gender awareness. Results: Globally, 430 participants completed the survey (68.4% were females). The 62.5% of male students had a poor knowledge of gender medicine. GRID score significantly differs between males and females (1.64±0.68 vs 1.51±0.49; p = 0.028). Males had lower GS scores (coefB -0.96, p < 0.05), while students who had a better knowledge on gender medicine (coefB 0.14, p < 0.05) and those who have received good example from tutors (coefB 0.14, p < 0.05) were more gender-sensitive. Older age (coefB 0.04, p < 0.05), a better knowledge on gender medicine (coefB 0.12, p < 0.05) and having had a tutor sensitive to gender issues (coefB 0.13, p < 0.05) were predictors of more stereotyped opinions towards patients. Having had a tutor aware of gender medicine (coefB 0.03, p < 0.05), male sex (coefB 0.12, p < 0.05) and older age (coefB 0.03, p < 0.05) were associated with more stereotypes towards doctors. Conclusions: Gender stereotypes are still common. During university courses and practical training more attention must be paid to explain that stereotyped gender differences are not scientifically proven and they do not contribute to provide better care. Therefore, the implementation of gender specific teaching throughout elective courses should be seriously considered. Key messages: Receiving more knowledge and more attention about gender medicine during university education was associated with higher gender stereotypes in our sample of medical students. Interventions in European university education are needed to make gender medicine education more effective in order to reduce gender stereotypes and contribute to better care.